2015
DOI: 10.3390/polym7121536
|View full text |Cite
|
Sign up to set email alerts
|

Metathesis Polymerization Reactions Induced by the Bimetallic Complex (Ph4P)2[W2(μ-Br)3Br6]

Abstract: Abstract:The reactivity of the bimetallic complex (Ph 4 P) 2 [W 2 (µ-Br) 3 Br 6 ] ({W 2.5 W} 7+ , a 12 e 3 ) towards ring opening metathesis polymerization (ROMP) of norbornene (NBE) and some of its derivatives, as well as the mechanistically related metathesis polymerization of phenylacetylene (PA), is presented. Our results show that addition of a silver salt (AgBF 4 ) is necessary for the activation of the ditungsten complex. Polymerization of PA proceeds smoothly in tetrahydrofuran (THF) producing polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The ratio of olefinic/aliphatic carbons depends on the mechanism of cross-linking and is equal to 4/3 (metathesis) and 2/5 (olefin coupling). Therefore, the olefin coupling contribution can be calculated via Equation (3), which takes the ratio of the integrated areas of the corresponding 13 C CPMAS peaks as input [16]. Thus, C olefinic refers to the total sp 2 carbons, C aliphatic to the total sp 3 carbons and x is the fraction of polymer double bonds that participate in cross-linking via olefin coupling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of olefinic/aliphatic carbons depends on the mechanism of cross-linking and is equal to 4/3 (metathesis) and 2/5 (olefin coupling). Therefore, the olefin coupling contribution can be calculated via Equation (3), which takes the ratio of the integrated areas of the corresponding 13 C CPMAS peaks as input [16]. Thus, C olefinic refers to the total sp 2 carbons, C aliphatic to the total sp 3 carbons and x is the fraction of polymer double bonds that participate in cross-linking via olefin coupling.…”
Section: Resultsmentioning
confidence: 99%
“…The use of bimetallic complexes with metal-metal bonds is less common [13,14], although they provide more precise control over stereoselectivity, since both metal centers can be involved in the reaction. We have previously reported that ditungsten clusters Na[W 2 ( μ -Cl) 3 Cl 4 (THF) 2 ]·(THF) 3 ({W 2 }, {W 3 W} 6+ , a′ 2 e′ 4 ) and (Ph 4 P) 2 [W 2 ( μ -Br) 3 Br 6 ] ({W 2.5 W} 7+ , a′ 2 e′ 3 ) are highly efficient and stereoselective room temperature homogeneous and/or heterogeneous initiators for the metathesis polymerization of alkynes [15,16] and the ROMP of norbornene derivatives [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the olefin coupling contribution can be calculated via equation (1) that takes the ratio of the integrated areas of the corresponding 13 C CPMAS peaks as input. 54 Thus, C olefinic refers to the total sp 2 carbons, C aliphatic to sp 3 carbons and x is the fraction of polymer double bonds that participate in crosslinking via olefin coupling. Integration of PNBD spectra provided an olefinic/aliphatic carbons ratio equal to 1.36 (Figure 19), showing that no crosslinking via olefin coupling takes place (x ≈ 0).…”
Section: Catalyst and Polymerization Reactionsmentioning
confidence: 99%
“…IV) towards the ROMP of NBE and derivatives has been also investigated 54. Despite the fact that bromide ligands are more labile than the chloride ones, addition of AgBF 4 is necessary in order to activate the ditungsten complex.…”
mentioning
confidence: 99%